Textbook of Clinical Pediatrics - Elzouki, A. Y.; Harfi, H. A.; Nazer, H.; Oh, William; Stapleton, F. B.; Whitley, R. J. (Springer Berlin Heidelberg : Imprint: Springer, 2012)
The second edition of the textbook is planned to become a MRW-textbook. It will be written by 389 eminent pediatricians and scientists from leading university hospitals and health centers in North America, Europe, Asia and Australia. Written with more than 425 chapters, the book will encompass virtually all pediatric subspecialties, covering every pediatric disease and organ system. Its strong clinical focus with a problem based approach will help practicing pediatricians, residents, medical students as well as family practitioners to manage sick children in a practical way, based on scientific evidence. Thus, it will become a valuable reference and resource for all health care practitioners dealing with pediatric patients.